Correlation between Skeletal Manifestations of Sickle Cell Disease (SCD) and Transcranial Doppler Imaging Velocities - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Context:Sickle cell disease (SCD), a genetic disorder, is a debilitating illness. Among the different complications of SCD, cerebrovascular complication results in stroke in pediatric population. The cause of stroke in those patients is attributed to vasculopathy, stenosis, or vaso-occlusion of distal internal carotid arteries. Another body system that is commonly affected is the musculoskeletal system. Both skeletal manifestations and vasculopathy in Circle of Willis in SCD are known consequences of the same underlying pathology.Aim:This study was conducted to assess the correlation between osseous findings and vasculopathy of Circle of Willis.Settings and Design:It was a chart review study conducted during December 2021 to January 2022. Children suffering from SCD were the study population.Materials and Methods:The sampling was done by using convenience purposive sampling technique. The data were collected as observations using picture archiving and communication system and then entered Excel spreadsheet.Statistical Analysis Used:The data were analyzed using SPSS, Version 28. The descriptive statistics including frequencies and percentages for the skeletal manifestations and transcranial Doppler imaging (TCDI) readings were calculated. To assess the association between skeletal manifestations and TCDI, a Chi-square test of independence was performed.Results:The findings showed that abnormal TCDI readings exhibited higher frequency on abnormal skeletal manifestations as compared to normal TCDI readings.Conclusion:The study showed that an osseous manifestation of disease was associated with vasculopathy of Circle of Willis vasculature. Therefore, osseous manifestations of SCD can be associated with the chance of stroke among the children since it is associated with the vasculopathy of Circle of Willis.